1989
DOI: 10.1007/bf00558163
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic study of the active metabolite of nabumetone in young healthy subjects and older arthritis patients

Abstract: We have performed a detailed pharmacokinetic study of the plasma concentrations of the major active metabolite of nabumetone, 6-methoxy-2-naphthylacetic acid (6 MNA), attained after a single dose and during chronic administration comparing the results of a group of young healthy volunteers with those of a group of elderly arthritic patients. The latter had higher peak plasma concentrations of 6 MNA and slower rates of elimination but there is no tendency for the drug to accumulate unpredictably in the old. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
6
1
1
Order By: Relevance
“…However, we analyzed also 6-MNA drug levels, which are in our study similar to those reported previously. 12,19 If the nabumetone exposition were higher by 2 orders of magnitude, significantly higher 6-MNA levels would be expected, which is not seen in the present study. Therefore, we assume that our observations are likely to be close to the drug levels in other studies, but this cannot be confirmed because the authors reported and analyzed 6-MNA only.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, we analyzed also 6-MNA drug levels, which are in our study similar to those reported previously. 12,19 If the nabumetone exposition were higher by 2 orders of magnitude, significantly higher 6-MNA levels would be expected, which is not seen in the present study. Therefore, we assume that our observations are likely to be close to the drug levels in other studies, but this cannot be confirmed because the authors reported and analyzed 6-MNA only.…”
Section: Discussioncontrasting
confidence: 62%
“…3,[8][9][10] nabumetone itself reaches considerably low plasma levels and its pharmacokinetics has been insufficiently described in humans, whereas the pharmacokinetics of 6-MNA has been well documented since preregistration studies. 11,12 High intersubject variability in drug absorption is indicated by extremely large range for t max from 1.5 to 48 hours. 5,11,12 Multiple peak concentrations, typically at 10 and 24 hours after nabumetone administration, have also been described on the pharmacokinetics (PK) profile of 6-MNA, 11,13 but the compound does not display usual characteristics leading to multiple peak PK (enterohepatic circulation, specific metabolism or absorption, etc).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-MNA competitively inhibits both cyclooxygenase isoenzymes, COX-1 and COX-2, by blocking arachidonate binding resulting in analgesic, antipyretic, and anti-inflammatory pharmacologic effects [5][6][7][8]. The enzymes COX-1 and COX-2 catalyze the conversion of arachidonic acid to prostaglandin G 2 (PGG 2 ), the first step of the synthesis of prostaglandins and thromboxanes that are generated in rapid physiological responses [9,10]. Nabumetone is used in the treatment of osteoarthritis, rheumatoid arthritis and other musculoskeletal disorders.…”
Section: Nabumetonementioning
confidence: 99%
“…Nabumetone is used in the treatment of osteoarthritis, rheumatoid arthritis and other musculoskeletal disorders. Preliminary studies to quantify this drug in biological fluids involved radioassay scintillation counting of isotopes and gas chromatography with flame ionization detection and reversed-phase highperformance liquid chromatography using violet or fluorescence detection [11][12][13][14][15][16]. 6-chloro-2-naphthylacetic acid [15], -naphtol [22] or naproxen [27,32] were used as internal standards for the determination in biological samples.…”
Section: Nabumetonementioning
confidence: 99%